Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan CV. Santoso Teknik Karawang - Lailatul Shalsabila; Aji Tuhagana; Zenita Apriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The main objective of this research is to assess the individual and combined impact of work discipline and work motivation on employee performance at CV Santoso Teknik Karawang. Descriptive and verification strategies were used in the quantitative analysis of this research. Fifty people from CV Santoso Teknik Karawang became the population or research subjects. Sampling using saturated sampling means conducting a survey of all workers at CV. Santoso Teknik Karawang has fifty employees. Data were collected via a Google Forms survey in which various items were rated using a Likert scale. Various data validity and reliability tests, as well as classic assumption tests are available in the SPSS version 22 application. Multiple linear regression, t-test, f-test, and coefficient of determination are part of this series of tests. Motivation and work discipline partially influence employee performance, based on the results of the t test. Apart from that, the f test confirms that there is a significant simultaneous influence between motivation and work discipline on the performance of CV Santoso Teknik Karawang..